RUANG MANUSIA DAN RUMAH TINGGAL SUATU TINJAUAN PERSPEKTIP KEBUDAYAAN - J. Lukito Kartono (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 1999)
In each culture,the understanding of space actually conveys various meanings.This philosophy of life leads to a dichotomy classification of the east and west culture.Since each has a cultural sub system,the term East and West cannot represent the existent phenomena in a wide scope.Therefore,some studies on human perception are applied to show the relationship between